Biological Prototype Acquisition Based on Biological Coupling in Bionic Design. (15th October 2022) - Bai, Zhonghang; Song, Meijia; Zhang, Xu; Zhang, Jiahui
Abstract : Because the judgment basis in the process of biological prototype screening is highly subjective, and because it is difficult to generate a scheme when using multiple biological prototypes for bionic design, this work proposes a biological prototype retrieval and matching method for multibiological prototype bionic design. Using BioTRIZ in combination with biological coupling mechanism analysis, orthogonal analysis, and the calculation of the goodness value of the scheme, a multibiological prototype bionic design model is constructed. First, the biological prototype contradictions matrix is obtained by BioTRIZ. Then, a biological coupling mechanism analysis is carried out to calculate the goodness value of the auxiliary scheme to further evaluate the advantages and disadvantages of the biological prototype. The orthogonal analysis is then conducted to select the optimal biological prototype combination scheme. Finally, the best biological prototype combination scheme is transformed into the final design scheme according to the biological coupling mode prompts. According to this process, the innovative design of an automatic food threading machine was carried out, and an experiment was conducted for verification. The results demonstrate that the machine after bionic improvement could meet the design requirements, and the feasibility and effectiveness of the established design model were verified.